2002
DOI: 10.1038/sj.mp.4000916
|View full text |Cite
|
Sign up to set email alerts
|

Codon 311 (Cys → Ser) polymorphism of paraoxonase-2 gene is associated with apolipoprotein E4 allele in both Alzheimer's and vascular dementias

Abstract: The gene of an esterase enzyme, called paraoxonase (PON, EC.3.1.8.1.) is a member of a multigene family that comprises three related genes PON1, PON2, and PON3 with structural homology clustering on the chromosome 7. 1,2 The PON1 activity and the polymorphism of the PON1 and PON2 genes have been found to be associated with risk of cardiovascular diseases such as hypercholesterolaemia, non-insulin-dependent diabetes, coronary heart disease (CHD) and myocardial infaction. 3-8 The importance of cardiovascular ris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
1
1

Year Published

2003
2003
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 24 publications
0
10
1
1
Order By: Relevance
“…For example, the most top selected SNPs in HGM-FS method in multiclass classifications come from gene “CTNNA3,” which is a protein-coding gene and is associated to late-onset Alzheimer's disease (Miyashita et al, 2007 ). The most top selected SNPs in SMML method in multiclass classifications come from gene “PON2,” which encodes paraoxonase-2 gene and is associated with apolipoprotein E4 allele in both Alzheimer's and vascular dementias (Janka et al, 2001 ). The most top selected SNPs in MKL method in multiclass classifications also come from gene “CTNNA3” and gene “PON2.” Although the well-known APOE SNP is not the top one SNP in our list, it still appears in the top rank list.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the most top selected SNPs in HGM-FS method in multiclass classifications come from gene “CTNNA3,” which is a protein-coding gene and is associated to late-onset Alzheimer's disease (Miyashita et al, 2007 ). The most top selected SNPs in SMML method in multiclass classifications come from gene “PON2,” which encodes paraoxonase-2 gene and is associated with apolipoprotein E4 allele in both Alzheimer's and vascular dementias (Janka et al, 2001 ). The most top selected SNPs in MKL method in multiclass classifications also come from gene “CTNNA3” and gene “PON2.” Although the well-known APOE SNP is not the top one SNP in our list, it still appears in the top rank list.…”
Section: Resultsmentioning
confidence: 99%
“…Although the APOE epsilon 2 displayed an increased risk for AMD, it did not approach statistical significance. The APOE epsilon 4 association with AMD is intriguing, since it is known to be a strong risk factor for Alzheimers disease (36,41,89), also a disease of old age.…”
Section: The Apoe Genementioning
confidence: 99%
“…PON2 deficiency in mice increases the risk of oxidative stress-related pathophysiological conditions such as development of atherosclerotic lesions [27], [28]. Furthermore, numerous studies on several human populations reported the association of PON2 polymorphisms with severe ischemic stroke [32], sporadic amyotrophic lateral sclerosis (SALS) [33], [34], [35], asthma [36] and Alzheimer's disease (AD) [37], [38]. Polymorphisms in another PON member, PON1, have also been associated with susceptibility to PD [39], [40].…”
Section: Introductionmentioning
confidence: 99%